What Does It Mean to Be Human? A Feminist and Anti-Racist Critique T&T Clark Reader in Theological Anthropology, Marc Cortez and Michael P. Jensen (eds), Bloomsbury T&T Clark, 2018 (ISBN 978-0-567-65557-8), viii + 424 pp., pb £33.99 ReSourcing Theological Anthropology: A Constructive Account of Humanity in the Light of Christ, Marc Cortez, Zondervan, 2017 (ISBN 978-0-310-51643-9), 304 pp., pb 29.99 - O'Donnell, Karen (Reviews in religion and theology, 2018)
Examination and analysis of two recent publications on theological anthropology, one a monograph and the other an anthology of key texts co-edited by the author of the monograph, raises questions of who is included and excluded in theological writing which considers what it means to be human. I argue that when the white male voice is privileged in these kinds of volumes, to the marginalization of the voices of women, of people of color, of LGBTQI people, of differently abled people, then the answer to this question—what does it mean to be human?—is skewed and incomplete. As theologians and teachers, we have a responsibility in our citation and text-selection practices to be critically reflective about who we include: such selections are politically, pedagogically, and theologically significant.